THE ROLE OF INDEPENDENT EXTRACURRICULAR WORK OF STUDENTS IN THE STRUCTURE OF THE EDUCATIONAL PROCESS AT THE DEPARTMENT OF INTERNAL MEDICINE - Гончарук, Людмила; Поддубная, Антонина; Баланюк, Ирина; Шулякова, Мар'яна; Пєстова, Аліна (SWorldJournal, 2022)
Purposeful set of actions of the student under the guidance of the teacher on the basis of support of educational process provides independence - possibility to carry out independent work on the basis of formation of qualities of reflective management, st